Optimum operational conditions for mixotrophic microalgae growth and nutrient recovery. Issue 1 (September 2021) - Oz, C; Fletcher, L; Camargo-Valero, M A
Abstract: Microalgae have been presented as microorganisms with great potential to recover nutrient from wastewater. Mixotrophic cultivation of microalgae in nutrient rich wastewater can help eliminating the deficiencies of both phototrophic and heterotrophic growth by allowing the independent optimisation of respiration and photosynthesis processes. Nutrient control and uptake by mixotrophic microalgae can be achieved either in a single or two-stage process using sequential reactors in a continuous flow system. Therefore, this work aims at studying mixotrophic microalgae growth in a two-stage biological process under continuous flow conditions with biomass recycle to recover nutrients from wastewater, considering the effects of different operational conditions (hydraulic retention time (HRT), cell retention time (CRT) and different nitrogen sources). The optimum operational conditions for algal nutrient uptake were identified to be 48 h HRT and 14 d CRT, using a mix of nitrogen sources (Ammonium-N to Nitrate-N ratio of 1:1) with 40.0% and 93.2% of phosphorus of nitrogen recovery in algal biomass, respectively.